2017
DOI: 10.1016/j.bbamem.2017.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Influence of membrane composition on the binding and folding of a membrane lytic peptide from the non-enveloped flock house virus

Abstract: Using a combination of coarse-grained and atomistic molecular dynamics simulations we have investigated the membrane binding and folding properties of the membrane lytic peptide of Flock House virus (FHV). FHV is an animal virus and an excellent model system for studying cell entry mechanisms in non-enveloped viruses. FHV undergoes a maturation event where the 44 C-terminal amino acids are cleaved from the major capsid protein, forming the membrane lytic (γ) peptides. Under acidic conditions, γ is released fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
20
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 59 publications
3
20
1
Order By: Relevance
“…Flock house virus (FHV), a member of the family Nodaviridae , was first isolated from a grass grub ( Costelytra zealandica ) in New Zealand [ 1 ]. It is a small non-enveloped virus comprising an icosahedral protein capsid and a single-stranded RNA genome of positive polarity [ 2 , 3 ]. Studies on FHV infection and the replication of its genome have provided valuable insights about virus entry and assembly [ 3 ], and antiviral immune response [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Flock house virus (FHV), a member of the family Nodaviridae , was first isolated from a grass grub ( Costelytra zealandica ) in New Zealand [ 1 ]. It is a small non-enveloped virus comprising an icosahedral protein capsid and a single-stranded RNA genome of positive polarity [ 2 , 3 ]. Studies on FHV infection and the replication of its genome have provided valuable insights about virus entry and assembly [ 3 ], and antiviral immune response [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…We found that γ 1 does not unfold and remains embedded in the membranes throughout 1-μs simulations. From these observations, we proposed that an energy barrier separates the folded state from the low helicity state, and the barrier height has a dependence on the amount of charge in the membrane [37]. Our equilibrium simulations were likely trapped in a metastable state, due to the rough energy landscape, which was insurmountable by conventional simulation approaches.…”
Section: Introductionmentioning
confidence: 88%
“…In our previous work [37], we investigated the thermodynamic aspects of binding and the structural dynamics of the FHV 21 N-terminal residues of the γ peptide (known as γ 1 ) using a multi-scale approach. We examined the binding and folding characteristics of γ 1 on pure phosphatidylcholine (PC), pure phosphatidylglycerol (PG) and a 50:50 mixed PC:PG membrane.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations